Prostaglandin E2 Receptor 3 (EP3) Contributes to Polyuria, Glomerular Hyperfiltration, and Renal Injury in Diabetes - Hassouneh, Ramzi (Université d'Ottawa / University of Ottawa, 2015)
Cyclooxygenases (COXs) and their main renal product, prostaglandin E2 (PGE2), regulate many physiological renal functions and are involved in the pathogenesis of diabetic kidney disease. The PGE2 receptor EP3 has been repeatedly shown to be upregulated during diabetes. Physiologically, EP3 is best recognized to act as a diuretic by antagonizing arginine-vasopressin (AVP)-mediated water reabsorption. Incidentally, the first renal manifestation of diabetes is polyuria, which may trigger a cascade of events leading to DN. We hypothesize that EP3 contributes to polyuria and kidney dysfunction during diabetes. We injected EP3-/- mice with streptozotocin (STZ) and evaluated their renal function 12-weeks post injection. EP3-/- STZ mice exhibit attenuated polyuria while exhibiting increased urine osmolality suggesting enhanced water reabsorption. Western blots reveal that EP3-/- STZ mice have increased expression of aquaporin-1 and aquaporin-2 as well as reduced urinary AVP excretion compared to STZ mice. However, salt transporters were equivalently increased in STZ and EP3-/- STZ mice. In vitro microperfusion shows that EP3 completely abrogates AVP-mediated water reabsorption in STZ cortical collecting ducts. Furthermore, EP3-/- STZ mice showed blunted renal COX-2 expression as well as reduced renal hypertrophy, glomerular hyperfiltration, and albuminuria. Taken together, the data suggests that EP3 contributes to polyuria during diabetes by inhibiting expression of aquaporins. Additionally, EP3 seems to contribute to renal COX-2 induction during diabetes. The lack of an increase in renal COX-2 protein levels in EP3-/- STZ mice may be protective by preventing further renal damage.
Keywords: Diabetes; Chronic Kidney Disease; Prostaglandins; Water Transport; Arginine Vasopressin; Collecting Duct